Effect of Burner Operation on the Catalyst Tube Lifetime of a Steam Methane Reformer: A Numerical Study - Chun-Lang Yeh (Applied Sciences, 2020)
In this paper, the catalyst tube lifetime of a practical steam methane reformer is analyzed numerically. The effect of burner operating mode on the flow development, hydrogen yield, and catalyst tube lifetime is discussed, with the aim of improving the reformer performance. The results of this study reveal that using the periodic boundary conditions, the temperatures and hydrogen yields obtained are much lower than the experimental values and the pressures are much lower than those using the real model. This results in overestimating the catalyst tube lifetime and underestimating the reformer operation risk. The catalyst tubes in the downstream area have longer lifetimes, while those in the upstream area have shorter lifetimes. Turning the upstream burners off is more efficient to the catalyst tube lifetime, while turning off the central groups of burners is less efficient. The main drawback of turning off burners is the decrease of hydrogen yield.